Note from the Guest Editor - Zincume, Philani (The South African Journal of Industrial Engineering, 2025)
"Alone we can do so little; together we can do so much." Helen Keller This year, the annual Special Edition features the top-rated research from three major conferences hosted across South Africa in 2025. These conferences are the 35th Conference of the Southern African Institute for Industrial Engineering (SAIIE35), the 26th Conference of the Rapid Product Development Association of South Africa (RAPDASA), and the 2025 Production and Operations Management Society (POMS) Africa International Conference. For the first time, this Special Edition includes contributions from POMS, an international organisation that represents the global community of supply chain, production, and operations management professionals. The inclusion of POMS Africa reflects a growing network of collaboration and knowledge exchange within our broader community. The volume is our largest Special Edition to date, with 28 articles that reflect a wide range of Industrial Engineering and related research. The strong participation from universities and universities of technology highlights an active Industrial Engineering presence across South Africa. The papers included in this Special Edition underwent the same double blind peer review process as the journal, with criteria equal to those of the journal. The papers selected for publication were based on reviewer scores, followed by a final check by the journal editors to ensure a high standard and suitability across the volume. We trust that the contributions in this volume will provide valuable insight and support continued growth in our field. Philani Zincume Guest editor